Penerapan Sistem Informasi Akuntansi Pada Pondok Pesantren Di Kota Madiun - Siti Suharni; Syarifah Ratih Kartika Sari (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2019)
Accountancy Information System is a system made by human beings consists of components in an organization to accomplish a goal, e.g. presenting information. Therefore, employing information system in pondok pesantren is absolutely necessary. Besides for adding efficiency and effectiveness of financial operational in pesantren, it also helps presenting aiding progress report given. Information resulted by Accountancy Information System holds an essential role. It can be used to monitoring, controlling medium, and managing all activity and financial operational activity of pondok pesantren in order to be running well. This study has general objective, e.g. understanding how good system for pesantren is. While specific objective of this study is understanding design of accountancy information system of Madiun City Boarding School. This study employs descriptive-qualitative approach that aims to describe object of research by collecting data. Data are collected through observation, interview, and documentation. Analysis of this study includes analysis on organizational structure, analysis of document used, and analysis of procedure implemented.